Day 3 Thu, February 03, 2022 2022
DOI: 10.2118/209144-ms
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Hydraulic and Conductive Half Lengths in the Bakken/Three Forks Play – Coupling Sealed Wellbore Pressure Monitoring SWPM & Chow Pressure Group CPG

Abstract: In development of the Bakken/Three Forks play, it is crucial to obtain a strong understanding of not just the hydraulic fracture geometry, but also what portion of those hydraulic fractures are conductive. If both parameters and their interactions are not fully understood, then development of the play could be severely compromised due to unoptimized well spacing and completion design. This study represents a two-pronged approach to better understand this interaction. The first step was to perform a Sealed Well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Chu et al (2020) propose that CPG less than 0.5 corresponds to weak interference, 0.5-0.75 as moderate interference, and CPG greater than 0.75 corresponds to strong interference. Detailed explanation of the CPG methodology is provided by (Ballinger et al, 2022).…”
Section: Review Of the Existing Cpg Based Methodology To Quantify Int...mentioning
confidence: 99%
“…Chu et al (2020) propose that CPG less than 0.5 corresponds to weak interference, 0.5-0.75 as moderate interference, and CPG greater than 0.75 corresponds to strong interference. Detailed explanation of the CPG methodology is provided by (Ballinger et al, 2022).…”
Section: Review Of the Existing Cpg Based Methodology To Quantify Int...mentioning
confidence: 99%
“…Chu et al (2020) state that CPG less than 0.5 corresponds to weak interference, 0.5-0.75 as moderate interference, and CPG greater than 0.75 corresponds to strong interference. Detailed explanation of the CPG methodology is provided by Ballinger et al (2022).…”
Section: Review Of the Existing Cpg Based Methodology To Quantify Int...mentioning
confidence: 99%
“…The closer CPG is to 1 the higher the connectivity. The lower the CPG (less than 0.5) the lower the connectivity between wells [62]. Almasoodi et al [63] reported that The CPG (Cross-Well Pressure Gradient) has certain limitations, including the inability to provide a quantitative estimate of how a well's production is affected by neighboring wells.…”
Section: Diagnostics Technologiesmentioning
confidence: 99%